WACANA MISOGINIS DALAM DISKURSUS TAFSIR AKADEMIS (KAJIAN EPISTEMOLOGIS ATAS JURNAL TAHUN 2010-2019) - Sherly Dwi Agustin (Universitas Nurul Jadid, 2020)
This study aims to examine misogynic interpretation issues in journals published in 2010-2019. Based on the assumption of journal stagnation in Indonesia on women studies, this study examined 32 journals published that year. Through an epithemological study, using literature review research methods and a philosophical approach, this study tries to examine bibliographically the articles that discuss the interpretation of misogyny verses. This study was conducted to analyze the tendency of writing on misogyny issues in journals. With Ignaz Goldziher's theory of the history of ideas, studies have succeeded in revealing that articles in journals tend to be based on interpretations of the formative era with quasi-critical reasoning dominated by modern feminist ideas from both the theme and methodological aspects. The implication of this study is the formation of a typology of misogynistic studies in journals, which can be used as a reference for the development of further studies, especially the development of the epistemology of al-Qur'an studies